Single stuck-at-faults detection using test generation vector and deep stacked-sparse-autoencoder - Malihi, Leila; Malihi, Razieh (SN applied sciences, 2020)
This paper proposed a new method for testing digital circuits without hardware implementation. This data-based method detects hundreds of single stuck-at faults in the ALU circuits, utilizing deep stacked-sparse-autoencoder (SSAE). ATALANTA software is one of the free automatic test pattern generation tools which cover faults in high accuracy. Test vectors which are extracted from bench circuits via ATALANTA software are the key point of the paper. Fault detection is introduced as a two-class problem. SSAE network is trained using the test vectors. Dimension reduction is done automatically in SSAE. Network performance is tested by changing sparse coefficients, number of stacked autoencoder and data augmentation. The results of this step are compared with the traditional multilayer perceptron classification. In this method, unlike SSAE, a manual method of reducing the dimension and extracting the feature is used. Fault coverage of ATALANTA software is over than 94%. Finally, the results obtained from the deep neural network show its significant performance in the circuit faults detection automatically.